Characterization of three yeast copper-zinc superoxide dismutase mutants analogous to those coded for in familial amyotrophic lateral sclerosis. - Nishida, C R (1994)
Sequences encoding three copper-zinc superoxide dismutase (CuZnSOD) mutant proteins analogous to those coded for in familial amyotrophic lateral sclerosis (fALS) were constructed in the Saccharomyces cerevisiae CuZnSOD gene and expressed in yeast lacking CuZnSOD (sod1-). Gly85-->Arg CuZnSOD failed to rescue the oxygen-sensitive phenotype of sod1- yeast, but Gly93-->Ala CuZnSOD and Lys100-->Gly CuZnSOD were apparently fully functional in vivo. The Gly85-->Arg mutant protein was purified and its metal-binding properties and SOD activity were found to be significantly altered relative to wild type. The Gly93-->Ala CuZnSOD was likewise purified but, in contrast, demonstrated metal-binding comparable to wild type and activity 80% that of wild type. These results suggest that SOD activity of human fALS mutant CuZnSODs may vary considerably in vivo, with at least some of them retaining a considerable amount of activity. Alternative theories to increased free-radical damage should be considered in attempting to explain fALS.